2016
DOI: 10.4238/gmr.15028284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the house dust mite allergen Der p 1 on tryptase release from human mast cells

Abstract: ABSTRACT. This study aimed to investigate the effects of the house dust mite allergen Der p 1 on the secretion of tryptase from the human mast cell line HMC-1. Flow cytometry was used to determine the expression levels of protease-activated receptor-2 (PAR2) on the surface of HMC-1 cells. HMC-1 cells were treated with Der p 1, SLIGRL-NH 2 (PAR2 agonist), LRGILS-NH 2 (control peptide for PAR2), or Der p 1 + FSLLRY (PAR2 antagonist), and the tryptase levels were measured using enzyme-linked immunosorbent assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, an anti-ICAM-1 antibody suppressed the tryptase-provoked mast cell accumulation, confirming that tryptase-induced mast cell recruitment was also dependent upon ICAM-1 activity. Tryptase and proinflammatory cytokines such as IL-18 have been reported to correlate well in the plasma of moderate and severe asthmatic patients (Wang et al, 2016). Moreover, tryptase and a PAR2 agonist peptide induced a substantial amount of IL-18 release in mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, an anti-ICAM-1 antibody suppressed the tryptase-provoked mast cell accumulation, confirming that tryptase-induced mast cell recruitment was also dependent upon ICAM-1 activity. Tryptase and proinflammatory cytokines such as IL-18 have been reported to correlate well in the plasma of moderate and severe asthmatic patients (Wang et al, 2016). Moreover, tryptase and a PAR2 agonist peptide induced a substantial amount of IL-18 release in mice.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, tryptase and a PAR2 agonist peptide induced a substantial amount of IL-18 release in mice. Another study has demonstrated that house dust mites induced the tryptase secretion from a human mast cell line by activating PAR2 receptors on the cell surface, suggesting the role of serine protease/ PAR2 signaling in allergic inflammation (Wang et al, 2016). Overall, serine protease inhibitors or PAR2 antagonist peptides may be promising therapeutic tools for the management of AD.…”
Section: Discussionmentioning
confidence: 99%